Some Alternatives for Reducing the Black-White Unemployment Rate Differential - Gregory, Karl D (American Economic Review, 1976)
Economic development involves promoting higher standards of living in part through generating saving for adding to the capital stock and productive potential of a community. Saving is a function of income. Most income is obtained from wages and salaries. It is therefore quite appropriate that this American Economic Association-National Economic Association session on Trend and Analysis in Black Economic Development include a paper on recent changes in the work status of blacks. Such a focus has been made more timely by the recent recession during which unemployment rates peaked at 8.9 percent in 1975-II, and for blacks, at 14.3 percent. Making matters worse, this was accompanied by a rate of inflation in the recession, the deepest of all since the Great Depression, which rose to double digit levels in 1974 and was over 7 percent in 1975. Measurement of the unequal work status among blacks and whites in the United States involves, among other factors, differences in labor force participation rates, unemployment rates, discouraged worker rates, underemployment rates, working conditions, and levels of wages, fringe benefits and other compensation. This paper discusses primarily only one attribute of work status, unemployment, despite the incompleteness of this concept. (Other research in which I am currently engaged, along with associates in the Congressional Budget Office, will analyze the other attributes.) The paper summarizes the recent behavior of the black-white unemployment differential, reviews the likely impact on the differential of two recovery paths, one for moderate recovery and another for rapid recovery by 1978-IV, and briefly suggests some alternative selective programs for narrowing the black-white differential in a short time period. I shall try to share with you some of the tentative and preliminary conclusions on these matters produced by ongoing research at the Congressional Budget Office.